Tisza River Valley: future prospects - Nagy, István; Ligetvári, Ferenc; Schweitzer, Ferenc (Hungarian Geographical Bulletin, 2010)
Hungary is among the countries in Europe most severely endangered by floods. Fourteen rivers entering Hungary from the mountainous area of the Carpathian Basin have high channel slope gradients which serve as a source of considerable flood hazard. The disastrous floods during the last decades in Hungary have been caused mainly by Tisza River and their tributaries situated on the eastern part of the Great Hungarian Plain (Alföld). These cases make necessary a thorough analysis of the extreme flood events to be carried out and the drawing of conclusions with recommendations to be made as for the immediate legal interventions. The present article outlines a river regulation program on the basis of a new concept. The purpose of this program beyond the increase of flood security is to improve the quality of life of the population concerned, extend water supply capacities, preserve natural resources and to provide flood risk management.